2018
DOI: 10.1053/j.gastro.2018.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Scoring System to Predict Outcomes of Vedolizumab Treatment in Patients With Crohn’s Disease

Abstract: We developed and validated a scoring system to identify patients with CD most likely to respond to 26 weeks of vedolizumab therapy. Further studies are needed to optimize its accuracy in select populations and determine its cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 36 publications
1
92
4
Order By: Relevance
“…Methodology for the development and validation of our CDST has been published previously. 13 In the current study, individual participant data from the phase 3 VDZ in CD trial (GEMINI 2) were used in combination with observational cohort data from the VICTORY consortium and GETAID collaboration. 14,15 A treat-straight-through cohort was created from the GEMINI 2 clinical trial programs to mimic an observational cohort design.…”
Section: Data Sources and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Methodology for the development and validation of our CDST has been published previously. 13 In the current study, individual participant data from the phase 3 VDZ in CD trial (GEMINI 2) were used in combination with observational cohort data from the VICTORY consortium and GETAID collaboration. 14,15 A treat-straight-through cohort was created from the GEMINI 2 clinical trial programs to mimic an observational cohort design.…”
Section: Data Sources and Participantsmentioning
confidence: 99%
“…The VICTORY consortium investigators previously developed and validated a clinical decision support tool (CDST) that classifies CD patients according to low, intermediate and high probability of response to VDZ . In the current analysis, we used the GEMINI 2 clinical trial data (NCT00783692) to assess whether these differences were related to differences in measured VDZ concentrations (exposure‐efficacy) and whether the CDST predicts differences in rapidity of onset of action.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic backgrounds and phenotypes of inflammatory bowel disease differ considerably between Asian and Western patients [10,11]; it is therefore important to determine treatment targets, outcomes, and responses in populations with different genetic backgrounds [12]. Multivariable analysis of GEMINI 2 data identified that ethnicity was a predictive factor of remission (American Indian or Alaskan Native, Asian, Black, and Native Hawaiian or other Pacific Islander vs non-Hispanic/Latino; odds ratio [OR] and 95% confidence interval [CI], 0.30 [0.12-0.75]) [13], and a post hoc analysis of data from GEMINI 2 and 3 also showed that race (non-White vs White) tended to predict rapid response to vedolizumab at Week 2 [14]. Therefore, it is meaningful to evaluate vedolizumab efficacy and associated predictive factors in patients with CD who are of different race to the more widely studied Western patient population.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical settings, morphological MRI coupled to molecular imaging of MAdCAM-1 could allow fast, sensitive and non-invasive evaluation of mucosal lesions, thereby alleviating the need for endoscopy and improving patient comfort and safety. The ability to detect MAdCAM-1 could also be key for the identification of patients candidate for MAdCAM-1 targeted therapies such as vedolizumab( 24 ). Beyond mucosal lesions, this method has also the potential to improve the diagnosis of other disorders involving dysregulation of MAdCAM-1 such as pancreatic cancers( 25 ) or chronic inflammatory liver disease( 26 ).…”
Section: Discussionmentioning
confidence: 99%